Estimates of the economic damages of an oil spill on the coast of Muara Gembong, Bekasi Regency, West Java, Indonesia - Novianti, Naomi; Hardiyanti, Armeita Rifqi; Afifah, Ifa; Ismiah, Salasatin (UIN Sunan Ampel Surabaya, 2022)
Coastal Muara Gembong is included in the Environmental Strategic Area, and the Natural Resources Strategic Area based on the Bekasi Regency Regional Spatial Plan 2011-2031. The Java Sea as the northern boundary of Bekasi Regency, one of the busy shipping routes originating from Tanjung Priok to Jayapura and Tanjung Priok to Surabaya, is the main source of oil spills that can occur around the coastal area of Muara Gembong. The coastal area of Muara Gembong has been affected by the Pertamina oil spill since July 21, 2019. The purpose of this study is to estimates the economic damages due to oil spills at Muara Gembong mangrove ecosystem. The economic damages are calculated by including two components, namely compensable value and recovery costs. Compensable value obtained by assessing natural resource damage, i.e. mangrove ecosystem, includes both the value of direct benefits and indirect benefits, which is IDR 497,519,413,897.09. The value of the recovery cost is IDR 40,611,959,689.98. So, the economic losses due to the oil spill on the Muara Gembong mangrove ecosystem is IDR 538,131,373,587.08. Along with these results, the government must also immediately be able to identify the impacts and calculate the value of losses or economic impacts to optimize the response to oil spill incidents.